Understanding employee engagement theory, research, and practice - Byrne, Zinta S (Routledge, 2015)
Employee engagement is a novel concept that has been building momentum in recent years. Understanding Employee Engagement: Theory, Research, and Practice exposes the science and practice of employee engagement. Grounded in theory and empirical research, this book debates the definitions of engagement, provides a comprehensive evaluation of empirical findings in the engagement field including a focus on international findings, and offers implications for science and practice in organizations. Employers can learn how to foster and drive engagement to increase productivity and happiness, and researchers can master the existing engagement literature and begin to study the many propositions and new models Zinta S. Byrne, Ph.D. proposes throughout the book.